Celulitis infecciosa - Pilaguano Latacunga, Janeth Liliana (2018)
The cellulitis is an acute infectious process that affects the skin and soft tissues, is caused by a wide range of bacteria, most of skin infections are caused by streptococcus pyogenes and staphylococcus aureus, the clinical picture includes local manifestations such as edema, Erythema, pain and heat in the affected area and even systemic manifestations such as malaise and fever. It is usually located most often in lower limbs. The present clinical case was applied in patient of female sex of 55 years of age with medical diagnosis of infectious cellulitis, who decides to seek medical attention when presenting pain and swelling of the left upper limb after suffering trauma. The realization of the present has as main objective to apply the nursing care process in patient with infectious cellulitis, for that reason for its development is based on the taxonomy Nanda, Nic and Noc and the theory of valuation of Marjory Gordon with the 13 functional health patterns. The Nursing Care Process is an indispensable tool in the nursing field which allows to develop a care plan efficient, in order to meet the basic needs of human beings and also in order to achieve the restoration and maintenance of optimal state of health of the patient.